A Critical Assessment of Data Loggers for Farm Monitoring: Addressing Limitations and Advancing Towards Enhanced Weather Monitoring Systems - Eze, Val Hyginus Udoka; Okafor , Wisdom O.; Odo, Jonathan Ikechukwu; Ugwu, Chinyere N; Ogenyi , Ogenyi Fabian Chukwudi; Edozie, Enerst (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2023)
This comprehensive review examines thirty-nine data loggers and their associated literature, systematically critiquing their design and implementation. The integration of data loggers in farm monitoring proves cost-effective, enabling the simultaneous monitoring of multiple parameters without human intervention. The accrued data, when logged over time, contributes to more accurate weather predictions, empowering farmers to strategically plan for upcoming seasons. However, the review reveals a prevalent issue among existing data loggers: many cannot read and record various weather parameters concurrently, coupled with insufficient storage capacity. This limitation hinders their suitability for prolonged, unattended data storage. Additionally, a significant number of the reviewed data loggers lack long-range wireless data transmission capabilities, restricting effective weather monitoring from a distance. The findings underscore the need for researchers to focus on developing advanced long-range data logger systems with enhanced memory storage capacities to address these identified shortcomings.